Does the inclusion criterion of women's aggression as opposed to their victimization result in samples that differ on key dimensions of intimate partner violence? - Sullivan, Tami P; Titus, Jennifer A; Holt, Laura J; Swan, Suzanne C; Fisher, Bonnie S; Snow, David L (Violence against women, 2010)
This study is among the first attempts to address a frequently articulated, yet unsubstantiated claim that sample inclusion criteria based on women's physical aggression or victimization will yield different distributions of severity and type of partner violence and injury. Independent samples of African American women participated in separate studies based on either inclusion criterion of women's physical aggression or victimization. Between-groups comparisons showed that samples did not differ in physical, sexual, or psychological aggression; physical, sexual, or psychological victimization; inflicted or sustained injury. Therefore, inclusion criterion based on physical aggression or victimization did not yield unique samples of "aggressors" and "victims."
Keywords: Adult; African Americans; Aggression; Battered Women; Domestic Violence; Epidemiologic Studies; Female; Humans; Interpersonal Relations; Male; Patient Selection; Severity of Illness Index; Sexual Partners; Socioeconomic Factors; Wounds and Injuries